Unravelling the speciation of gold(I) fluorinated benzenethiolates using hyphenated HPLC/ICP-AES and HPLC/ESI-MS techniques; Talanta; Vol. 298, Pt. B - Volchek V. Victoria; Sheven Dmitriy G.; Tkachenko P. A. Pavel; Maksimov A. M. Aleksandr Mikhaylovich; Sokolov M. N. Maxim; Abramov P. A. Pavel Aleksandrovich (2026, 2026)
Title screen